Hubungan Motivasi Belajar dan Sumber Belajar dengan Hasil Belajar IPA Kelas V (Joyful Learning Journal, 2018)
This research was correlation research for knowing correlation of motivation learning and learning sources with science studying result of grade fiveth. The population were 246 national elementary school grade fiveth students of Gugus Dr. Cipto Mangunkusumo, Juwana, Pati Regency. Then, the sample were 100 students that taken by area sampling technique. The data collecting method were test and documentation. The data analysis technique were normality test, linearity test, descriptive statistical, and product moment test. The result of research showed that the correlation value of motivation learning and learning sources r count was bigger than r table, 0,686 > 0,195 and the significant F change value was lower than significant 5%, 0,000 < 0,05, so, there was significant correlation of motivation learning and learning sources with science studying result with strong significant. The contribution of motivation learning and learning sources with science studying result was 47%. So, it can be concluded that there was significant correlation of motivation learning and learning sources with science studying result of national elementary school grade fiveth students of Gugus Dr. Cipto Mangunkusumo, Juwana, Pati Regency.